Effect of damage on the etching and X-ray diffraction properties of zircon - Amin, Y.M. (Elsevier, 1988)
The etching time of zircons with different amounts of radiation damage is measured. It is found that as track density increases, a shorter etching time is needed to reveal the tracks. The change in X-ray diffraction angle (20) of the (112) plane for zircon with different amounts of radiation damage is also studied. A correlation is found between diffraction angle and fission track density. For zircon with natural track density of ≤ 3 x 106 tracks/cm2, there seems to be an inverse relation between track density and 20 values suggesting that as the degree of radiation damage of the crystal increases, more atoms are forced into interstitial positions. However beyond the track density of ∼ 3 x 106 tracks/cm2, the change in 20 with increasing track density is not as rapid as before, approaching a saturation value of 35.62o.